(untitled) (International Journal of Environmental Sciences, 2025)
Ehrlichia canis, the causative agent of canine monocytic ehrlichiosis (CME), is a globally important tick-borne pathogen in dogs. Current diagnostic methods such as PCR require advanced laboratory infrastructure, limiting their use in field settings. This study developed and validated a dual-format recombinase polymerase amplification (RPA) assay targeting the 16S rRNA gene of E. canis, incorporating both fluorescence-based real-time detection and lateral flow strip readouts. Primers and probes were designed using Primer-BLAST and optimized for RPA at 39 °C for 20 minutes. Analytical sensitivity reached 10 femtograms of genomic DNA ( 7–10 bacterial genomes), with 100% analytical specificity against related pathogens (Anaplasma platys, A. phagocytophilum, Rickettsia rickettsii). Clinical validation with 500 canine blood samples from Chennai, India, identified 43 positive cases (8.6% prevalence), achieving perfect concordance with conventional PCR (100% sensitivity and specificity; Cohen’s κ = 1.000). The fluorescence format provided semi-quantitative results with strong correlation between DNA concentration and threshold time (R² = 0.981), while the lateral flow format enabled simple visual interpretation within 30 minutes. The RPA assay demonstrated excellent reproducibility (CV < 7%), reagent stability at ambient temperature (>6 months), and 65% cost reduction compared to PCR. These results highlight the RPA assay as a rapid, accurate, and field-deployable diagnostic tool for CME, particularly suited to veterinary practice and surveillance in resource-limited, tick-endemic regions.